2021
DOI: 10.1109/tasc.2021.3053299
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Superconductor Coatings for Beam Impedance Reduction in Particle Colliders: Nonlinear Effects

Abstract: Coating of surfaces facing particle beams with High-Temperature Superconductors (HTS) for reducing the beam coupling impedance is being considered for the next generation of hadron colliders, such as the FCC-hh at CERN, where HTS would be exposed to the high-frequency wakefields generated by the particle bunches and to the strong field of the steering magnets. In this frame, we present a simple model for the calculation of the microwave response of HTS exposed to a strong external magnetic field, which takes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…( 1) and (2). A notable gain of several orders of magnitude is readily visible at low frequencies for both longitudinal and transverse resistive wall impedance, at which the highest instabilities for a copper beam screen are predicted [14]. As discussed in the previous section, the difference in the surface impedance frequency dependencies between Cu and REBCO-CCs is noticeable in both complex resistive wall impedance planes leading to unique impedance behaviours.…”
Section: Rebco-ccs Performance Requirements -mentioning
confidence: 70%
See 2 more Smart Citations
“…( 1) and (2). A notable gain of several orders of magnitude is readily visible at low frequencies for both longitudinal and transverse resistive wall impedance, at which the highest instabilities for a copper beam screen are predicted [14]. As discussed in the previous section, the difference in the surface impedance frequency dependencies between Cu and REBCO-CCs is noticeable in both complex resistive wall impedance planes leading to unique impedance behaviours.…”
Section: Rebco-ccs Performance Requirements -mentioning
confidence: 70%
“…In addition, the circulating proton bunches induced RF current interacts with the vortex lattice. The RF currents' Lorentz forces cause the vortex lattice to move in a lossy periodic manner, some forms of lattice motion involve net displacement of vortices, while others do not [7,14,15].…”
Section: Rebco-ccs Performance Requirements -mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation occurs in the REBCO-CCs in the FCC-hh BS where the vortices will be subject to a DC magnetic field perpendicular to the RF image currents induced by the beam. This scenario can give rise to a vortex oscillating motion [18] which may include net displacement. Hence, it is essential for the FCC-hh to determine whether the induced RF azimuthal magnetic field strength will be sufficient to fluctuate and/or displace the trapped vortices away from their static position.…”
Section: Flux Shakingmentioning
confidence: 99%
“…One such possibility is the use of high-temperature superconductors (HTS) which have transition temperatures above 90 K and surface resistances well below that of copper in the temperature range of interest [8], i.e. between 40 and 60 K. In recent years, several studies have shown the potential of REBa 2 Cu 3 O 7−x coated conductors (REBCO-CCs, RE = Y, Gd, Eu) as coating materials for the BS in order to minimize the beam impedance [9][10][11][12][13][14][15][16][17][18]. Even though these previous works on coated conductors have shown that their small-signal surface resistance is significantly below that of Cu, there are other aspects related to their surface impedance that may compromise their use in the FCC-hh BS, specifically [19][20][21][22][23][24][25]: its dependence on radio-frequency (RF) strength under large applied DC magnetic fields, and the appearance of temperature effects, including self-heating, resulting from the application of large RF fields.…”
Section: Introductionmentioning
confidence: 99%